A unified neurocognitive model of semantics language social behaviour and face recognition in semantic dementia - Junhua Ding (Nature Portfolio, 2020)
Semantic dementia patients present with a core semantic impairment and variations of language, behavioural and face recognition abilities. Here, the authors build a unified multidimensional model to capture all these graded symptoms and map them to the variations in the patients’ frontotemporal atrophy.